A Scoping Review of Workplace Interventions to Promote Positive Attitudes Toward Older Workers and Reduce Age-Based Discrimination - Sinclair, C.; Joffe, T.; Ginnivan, N.; Parker, Sharon; Anstey, K.J. (2024)
Population aging trends have created a need for effective policies to extend adult working lives. Previous research has identified the prevalence of negative attitudes (age-related stereotypes, prejudice, and discriminatory behaviors) directed toward older workers in the workplace context.The current scoping review aimed to describe and assess the current evidence in support of different types of interventions aimed at promoting positive attitudes and reducing age-based discrimination in the workplace context. A search of peer-reviewed and grey literature databases identified 22 relevant studies, including data from 5,078 adult participants, across laboratory and field settings. From examination of these studies, we propose and describe four thematic categories of interventions, as a way of organizing this literature: “de-biasing interventions,” “brief attitudinal interventions,” “age diversity workshop interventions,” and “structural or contextual interventions.” At the current point in time, studies assessing age diversity workshop interventions appear to be the strongest, having a clear theoretical basis, having a focus on interventions that can be delivered in workplace settings, and providing evidence for positive effects on measures that are meaningful for organizations and older workers. While a number of promising interventions have been tested, most studies were only able to demonstrate improvements in explicit measurements of attitudes toward older adults, immediately following the intervention. Collaborative partnerships with organizations and further high-quality studies (particularly in field settings) are required to support the development, evaluation, and implementation of interventions to promote positive attitudes toward older adults in real-world workplace settings.